2003
DOI: 10.1038/sj.mp.4001444
|View full text |Cite
|
Sign up to set email alerts
|

The molecular genetics of schizophrenia: new findings promise new insights

Abstract: The high heritability of schizophrenia has stimulated much work aimed at identifying susceptibility genes using positional genetics. However, difficulties in obtaining clear replicated linkages have led to the scepticism that such approaches would ever be successful. Fortunately, there are now signs of real progress. Several strong and well-established linkages have emerged. Three of the best-supported regions are 6p24-22, 1q21-22 and 13q32-34. In these cases, single studies achieved genome-wide significance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(186 citation statements)
references
References 143 publications
(132 reference statements)
3
177
1
4
Order By: Relevance
“…The observation of association with the opposite allele to the one initially reported by Stefansson and others for SNP8NRG221533 was disconcerting; however, a recent report from Bakker et al 35 reported overtransmission of the T allele as well. In the schizophrenia genetics literature, differing allele, SNP and haplotype associations across studies are common 39 and complicate the interpretation of these findings. Clearly, these statistical associations still require biological evidence to support them.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of association with the opposite allele to the one initially reported by Stefansson and others for SNP8NRG221533 was disconcerting; however, a recent report from Bakker et al 35 reported overtransmission of the T allele as well. In the schizophrenia genetics literature, differing allele, SNP and haplotype associations across studies are common 39 and complicate the interpretation of these findings. Clearly, these statistical associations still require biological evidence to support them.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has identified several schizophrenia risk genes, with varying levels of genetic, molecular biological, and theoretical evidence. 43,44 In particular, two leading schizophrenia risk genes, NRG1 and DTNBP1, have disease-associated polymorphisms that do not result in the expression of an abnormal protein in the manner generally found for classical Mendelian disorders. 45,12 A third explanation One hypothesized explanation for the diverse genetic associations found for schizophrenia is a 'polygene model,' where each gene locus has a small effect so that schizophrenia arises as the aggregate consequence some mixture of multiple risk genes or environmental factors.…”
Section: Epigenetic Factorsmentioning
confidence: 99%
“…1,2 In the last few years, however, the momentum of the positive studies has increased tremendously. Several genome-wide linkage studies have identified many regions that are now supported by data from multiple independent studies (see Levinson 3 and Owen et al 4 for review). In addition, meta-analyses have highlighted additional promising regions.…”
Section: Introductionmentioning
confidence: 96%